PENGARUH DINAMIKA KOMUNIKASI INTERPERSONAL TERHADAP PENINGKATAN KEINTIMAN ANAK DENGAN ORANG TUA YANG BEKERJA - Anizza Oktaviany, (2023)
Almost all heads of families have different family problems, some are well off and some are not well off, for some parents who have a poor economy they will work to supplement their income and spend time outside rather than at home, this is what causes communication between very few parents and children. The division of time and communication between family members becomes a new problem in everyday life which results in disharmony between children and parents. The type of research used is a quantitative research method with explanatory research and uses the Social Penetration Theory. This study uses a survey and uses interpersonal communication theory to analyze the problem. The data collection technique used in obtaining the research results was a questionnaire to 88 respondents using a sampling technique, namely proportional strata. Based on the results of the study that the dynamics of interpersonal communication has a significant influence on the intimacy of children with working parents. Interpersonal communication has an important and strong role in the intimacy of a family relationship to trust and be open to one another.